Integrated carbon / carbon composite material crucible containing yttrium oxide coating

By setting a glass-carbon coating and yttrium oxide coating in a carbon/carbon composite crucible, the heat resistance and cost problems of quartz crucibles in traditional single crystal silicon drawing furnaces are solved, and the crucible life extension and the purity of silicon material are guaranteed.

CN119552003APending Publication Date: 2025-03-04XIAN CHAOMA SCI TECH

Patent Information

Application Number
CN202411569334.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

In traditional single crystal silicon drawing furnaces, quartz crucibles are prone to deform and consume at high temperatures, and quartz sand raw materials are short of, resulting in high crystal drawing costs.

Method used

An integrated carbon/carbon composite crucible containing yttrium oxide coating is used, and the heat resistance and silicon corrosion resistance of the crucible are improved by providing a glass-carbon coating and a yttrium oxide coating on the inner surface of the carbon/carbon composite crucible body.

Benefits of technology

The service life of the crucible is extended, the crystal pulling cost is reduced, and the yttrium oxide coating does not introduce impurities, ensuring the purity of the silicon material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552003A_ABST
    Figure CN119552003A_ABST
Patent Text Reader

Abstract

The invention relates to an integrated carbon / carbon composite material crucible containing an yttrium oxide coating, and belongs to the technical field of thermal field parts for monocrystalline silicon. The crucible comprises a carbon / carbon composite material crucible body, a glassy carbon coating and an yttrium oxide coating, the glassy carbon coating can effectively relieve thermal mismatch between the yttrium oxide coating and the carbon / carbon composite material crucible body, and carbon in the carbon / carbon composite material crucible body can be effectively prevented from escaping; impurities are not introduced into the yttrium oxide coating in the silicon melting process, so that the purity of a silicon material can be effectively ensured, and the yttrium oxide coating has excellent silicon erosion resistance and high-temperature stability; the carbon / carbon composite material crucible body is formed by densifying a carbon fiber prefabricated body which is formed by needling and laying a pure net tire for spraying resin, and the inner surface of the carbon / carbon composite material crucible body is a net tire which is wholly approximately isotropic, so that the overall mechanical strength of the crucible can be ensured, and a good combination effect with a subsequent functional coating can be ensured; and the service life of the crucible can be prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an integrated carbon / carbon composite material crucible containing an yttria coating, and belongs to the technical field of thermal field components for single crystal silicon. Background Art

[0002] The single crystal silicon pulling furnace used in traditional single crystal silicon pulling is usually composed of a carbon / carbon crucible and a quartz crucible, that is, the quartz crucible is nested in the carbon / carbon crucible. The quartz crucible plays the role of carrying silicon materials to ensure the purity of silicon materials, while the carbon / carbon crucible plays the role of carrying the quartz crucible and providing strength support. The temperature inside the single crystal silicon pulling furnace is as high as 1500℃. The quartz crucible holding the silicon materials will have problems such as deformation and softening, and replacement is very frequent. About 1 carbon / carbon crucible will consume 12 to 18 quartz crucibles. In addition, the raw material quartz sand for the production of quartz crucibles is relatively scarce. In recent years, the rapid increase in the price of high-purity quartz sand and the imbalance between supply and demand have led to high crystal pulling costs.

[0003] Carbon / carbon composite materials are composite materials formed by carbon fiber or various carbon fabrics reinforced with carbon matrix. They have excellent properties such as low density, high specific strength, wear resistance, and high temperature resistance. They are currently widely used in aerospace, metallurgy, new energy and other fields. At present, researchers have proposed the use of "integrated carbon / carbon composite crucibles" to replace the traditional "combination of carbon / carbon crucibles and quartz crucibles". On the one hand, it can avoid the impact of the rapid rise in the price of high-purity quartz sand and reduce the material cost of crystal pulling. On the other hand, the integrated design can combine materials and performance into one, maximize its advantages, and further reduce product costs.

[0004] The integrated carbon / carbon composite crucible is formed by densifying the carbon fiber preform to form a carbon / carbon composite crucible body, and then preparing a high-performance coating on the inner surface of the carbon / carbon composite crucible body. For example, patent CN103102170A prepares SiC coating and Si on the inner surface of the carbon / carbon composite crucible body. 3 N 4 Coating can significantly increase the number of times the crucible can be used and significantly improve its life, but Si 3 N 4 The coating surface is relatively rough and has a certain wettability to silicon, which may damage Si in the production process of single crystal silicon. 3 N 4 Risks of coating.

[0005] In addition, the carbon fiber preform is the blank for preparing carbon / carbon composite crucibles, which directly affects the service life of crucible products. The disclosed carbon fiber preform is usually prepared by laminating a layer unit consisting of a carbon fiber woven cloth / carbon fiber mesh layer combined with a carbon fiber filament winding layer. Although the carbon fiber preform has high mechanical strength and good shaping effect, due to the presence of the carbon fiber woven cloth on its inner surface, the surface roughness is low and the bonding with the subsequent functional coating is poor, which will greatly affect the service life of the crucible product. Summary of the invention

[0006] In view of this, the present invention provides an integrated carbon / carbon composite material crucible containing an yttria coating, wherein a glassy carbon coating and an yttria coating are sequentially arranged on the inner surface of the carbon / carbon composite material crucible body, and the glassy carbon coating effectively alleviates the thermal mismatch between the yttria coating and the crucible body, and also has excellent performance in preventing carbon from escaping from the crucible body; the yttria coating does not introduce impurities during the silicon melting process, can effectively ensure the purity of the silicon material, and has excellent resistance to silicon corrosion. In addition, the carbon / carbon composite material crucible body is densely formed by a carbon fiber preform prepared by needle-punching a pure mesh tire and spraying a resin, and its inner surface is a mesh tire that is nearly isotropic as a whole, which can not only ensure the overall mechanical strength of the crucible, but also ensure a good combination effect with the subsequent functional coating, thereby increasing the service life of the crucible.

[0007] The objectives of the present invention are achieved through the following technical solutions.

[0008] An integrated carbon / carbon composite material crucible containing an yttria coating, the crucible comprising a carbon / carbon composite material crucible body, a glassy carbon coating and an yttria coating, wherein the glassy carbon coating is located between the carbon / carbon composite material crucible body and the yttria coating;

[0009] The carbon / carbon composite crucible body is prepared by carbon densification of a carbon fiber preform; the carbon fiber preform is a structure composed of alternately stacked carbon fiber mesh needle-punched layers and resin layers sprayed on the outer surface of the carbon fiber mesh needle-punched layers.

[0010] Furthermore, the thickness of the glassy carbon coating is 50 to 300 μm.

[0011] Furthermore, the thickness of the yttrium oxide coating is 100-500 μm.

[0012] Furthermore, the density of the carbon fiber preform is 0.30-0.50 g / cm 3 The density of the carbon / carbon composite crucible body is 1.50-1.70 g / cm 3 .

[0013] Furthermore, the glassy carbon coating is prepared by a resin impregnation carbonization process, which specifically includes the following preparation steps:

[0014] The carbon / carbon composite material crucible body is first impregnated in resin, impregnated for 0.5 to 5 hours at an impregnation pressure of 1 to 3 MPa, then heated to 100 to 300° C. at a heating rate of 1 to 3° C. / h and cured at 100 to 300° C. for 3 to 5 hours, then heated to 900 to 1100° C. at a heating rate of 1 to 5° C. / h and carbonized at 900 to 1100° C. for 5 to 10 hours, thereby forming the glassy carbon coating on the inner surface of the carbon / carbon composite material crucible body;

[0015] The resin is preferably furfural resin or phenolic resin.

[0016] Furthermore, the yttrium oxide coating is prepared by a plasma spraying process, and the process parameters of the plasma spraying include: the particle size of the yttrium oxide powder is 10 to 100 μm, the carrier gas (such as nitrogen) pressure is 0.2 to 3 MPa, the auxiliary gas (such as hydrogen) pressure is 0.1 to 2 MPa, the current is 300 to 900 A, the voltage is 40 to 120 V, and the spraying distance is 30 to 180 mm.

[0017] Furthermore, the carbon fiber preform is subjected to pyrolytic carbonization and resin carbonization densification treatment in sequence by using a chemical vapor infiltration process combined with a resin impregnation carbonization process, that is, the carbon fiber preform is first subjected to pyrolytic carbonization densification treatment by using a chemical vapor infiltration process and the density is increased to 1.0-1.20 g / cm 3 Then, the carbon fiber preform is subjected to resin carbon densification treatment by resin impregnation carbonization process and the density is increased to 1.50-1.70 g / cm 3 , then a carbon / carbon composite material crucible body is obtained;

[0018] Preferably, the parameters of the chemical vapor infiltration process are as follows: propylene or natural gas is used as the carbon source gas, the flow rate of the carbon source gas is 10-50 L / min, the deposition temperature is 900-1100°C, and the total deposition time is 80-120 h; the parameters of the resin impregnation carbonization process are as follows: furfural resin or phenolic resin is used as the impregnating agent, impregnated for 0.5-5 h at an impregnation pressure of 1.0-3.0 MPa, then cured at a curing temperature of 100-300°C for 1-10 h, and then carbonized at a carbonization temperature of 900-1000°C for 2-6 h, and the heating rate of the curing and carbonization process is 10-20°C / h.

[0019] Furthermore, the carbon fiber preform comprises the following specific preparation steps:

[0020] (1) A carbon fiber web is needle-punched and laid on a core mold to form a web layer;

[0021] (2) spraying a layer of resin on the surface of the web layer to form a resin layer;

[0022] (3) Repeating the operations of steps (1) to (2) multiple times, forming an alternating stacking structure of a web layer and a resin layer on the surface of the resin layer in step (2), until the desired thickness of the preform is reached after the last spraying of the resin, thereby obtaining a preform precursor;

[0023] (4) Curing the preform precursor obtained in step (3) to obtain the carbon fiber preform.

[0024] Furthermore, step (1) uses a soft core mold, which is convenient for needle punching, such as a wooden core mold or a rubber core mold; and before the curing treatment in step (4), the soft core mold is preferably replaced with a hard core mold, such as a metal core mold or a graphite core mold, to avoid deformation of the core mold during the curing treatment.

[0025] Furthermore, the carbon fiber mat is a thin felt made of chopped carbon fiber with a surface density of 50 to 500 g / m 2 .

[0026] Furthermore, the needle punching density of the web layer is 10 to 50 needles / cm 2 The acupuncture depth is 5 to 10 mm.

[0027] Furthermore, the resin used for spraying the resin layer is furfural resin or phenolic resin.

[0028] Furthermore, the resin spraying amount of the resin layer is 0.5 to 1.5 L / cm 2 .

[0029] Furthermore, the curing conditions are as follows: curing pressure is 1.0-3.0 MPa, curing temperature is 100-250° C., and curing time is 3-5 h.

[0030] Furthermore, according to the structure of the integrated crucible, from the upper part to the lower part of the crucible along its depth direction it is divided into a crucible straight section, a crucible R-angle transition section, and a crucible bottom surface. Then, the thickness of the crucible straight section in the carbon fiber preform is less than the thickness of the crucible R-angle transition section, and the thickness of the crucible R-angle transition section is less than or equal to the thickness of the crucible bottom surface.

[0031] Furthermore, the thicknesses of the straight section of the crucible, the R-angle transition section of the crucible, and the bottom surface of the crucible in the carbon fiber preform are 200-500 mm, 300-600 mm, and 400-800 mm, respectively.

[0032] Furthermore, a layer of web layer and a layer of resin layer form a layer unit, and the thickness of a layer unit is 5-10 mm. The difference in thickness of the crucible straight tube section, the crucible R angle transition section and the bottom surface of the crucible in the preform lies in the different number of layer units.

[0033] Beneficial effects:

[0034] (1) The present application sets a glassy carbon coating as a transition layer between the crucible body and the yttrium oxide coating. Compared with the traditional use of silicon carbide coating as a transition layer, the glassy carbon and the carbon in the crucible body are similar substances, with a high thermal match and better bonding with the crucible body. In addition, the porosity of the glassy carbon coating is approximately zero, which is denser than the silicon carbide coating, and can further enhance the ability to prevent carbon from escaping from the crucible body. The yttrium oxide coating used in the present application does not introduce impurities during the silicon melting process, thus meeting the requirements of crystal pulling. Moreover, the valence bond structure of yttrium oxide itself makes it difficult for silicon to enter the interior of yttrium oxide at high temperatures, and has excellent resistance to silicon corrosion. In addition, compared with aluminum oxide coating, yttrium oxide coating has higher temperature resistance, and no phase change occurs at high temperatures, further increasing the stability of yttrium oxide coating.

[0035] (2) The present application adopts a carbon fiber mesh with sprayed resin to prepare the carbon fiber preform of the crucible. On the one hand, the sprayed resin can play a mechanical supporting role between the mesh layers after curing treatment, ensuring the overall mechanical properties of the crucible product, and can also make the carbon fiber preform structure hardened and not easy to deform, which is more conducive to transportation and storage; on the other hand, the nearly isotropic pure mesh layer is used as the inner surface of the carbon fiber preform, which has a certain roughness and uniform surface quality, which is not only conducive to the preparation of the subsequent functional coating, but also improves the bonding performance of the functional coating with the crucible body, solving the problem of affecting the service life of the crucible product due to the easy shedding of the functional coating. In addition, compared with the carbon fiber preform made of carbon fiber woven cloth, carbon fiber mesh and carbon fiber filament, the process operation of the carbon fiber preform made of pure mesh in the present application is simpler and the preparation cycle is short.

[0036] (3) The resin impregnation carbonization process used in this application can meet the requirements of large-scale, batch-scale glassy carbon coating preparation. It should be noted that in the preparation of glassy carbon coating, the heating rate of the curing and carbonization process is an important factor affecting the density of the coating. If the heating rate is too fast, the glassy carbon coating will have defects such as microcracks and pores. If the heating rate is too slow, the production cost will be greatly increased.

[0037] (4) The present application utilizes plasma spraying technology to prepare yttrium oxide coatings, which have controllable thickness, low porosity, high quality consistency, high preparation efficiency, and are suitable for mass production.

[0038] (5) Based on the structural characteristics of the crucible itself, it can be seen that the stress concentration is the greatest at the R corner, which is prone to fatigue cracks. Increasing the thickness here can effectively make the straight tube section transition smoothly to the bottom surface, reducing the stress concentration problem at the R corner; in addition, affected by the actual working conditions, the R corner and the bottom surface are most affected by the gravity of the silicon melt. Increasing the thickness of these two places can effectively prevent the occurrence of "silicon leakage"; and setting different thicknesses for different areas can effectively reduce the overall weight of the crucible product and reduce the manufacturing cost of the crucible product on the basis of ensuring the overall mechanical properties of the crucible product. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 Schematic diagram of the structure of the integrated carbon / carbon composite material crucible containing yttria coating prepared in Example 1.

[0040] Among them, 1-carbon / carbon composite material crucible body, 2-glass carbon coating, 3-yttrium oxide coating. DETAILED DESCRIPTION

[0041] The present invention is further described below in conjunction with specific embodiments, wherein the methods are conventional methods unless otherwise specified, and the raw materials can be obtained from public commercial channels unless otherwise specified. In addition, in the description of the present invention, it should be understood that the orientations or positional relationships indicated by the terms "upper", "lower", "front", "back", "left", "right", "top", "bottom", "inside", "outside", etc. are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation to the present invention.

[0042] Example 1

[0043] The integrated carbon / carbon composite material crucible containing the yttria coating 3 specifically comprises the following preparation steps:

[0044] (1) A carbon fiber mesh is needle-punched and laid on a wooden core mold to form a mesh layer;

[0045] Among them, the carbon fiber mesh tire is made of short-cut carbon fiber with a surface density of 50g / m 2 The felt has a needle density of 10 needles / cm 2 , the needling depth is 5 mm; the wooden core mold is made based on the inner surface structure and size of the integrated crucible;

[0046] (2) Spray a layer of furfural resin on the surface of the web layer at a spray volume of 0.5L / cm 2, forming a resin layer; at this time, the web layer after spraying the furfural resin is a ply unit (comprising the web layer in step (1) and the resin layer in step (2)), and the thickness of the ply unit is 5 mm;

[0047] (3) Repeating steps (1) to (2) multiple times, forming an alternating stacking structure of a web layer followed by a resin layer on the surface of the resin layer in step (2) (i.e., stacking multiple layer units on the layer units formed in step (2)), until the desired thickness of the preform is reached after the last spraying of the resin, thereby obtaining a preform precursor;

[0048] According to the structure of the integrated crucible, the crucible is divided into a straight section, a R-angle transition section, and a bottom surface of the crucible in sequence from the upper part to the lower part along its depth direction. Different numbers of layering units are used to make the thickness of the straight section, the thickness of the R-angle transition section, and the thickness of the bottom surface of the crucible 200 mm, 300 mm, and 400 mm, respectively.

[0049] (4) The wooden core mold in the preform precursor obtained in step (3) was replaced with a graphite core mold, and then placed under a pressure of 1.0 MPa and a temperature of 250° C. for curing for 3 h to obtain a density of 0.30 g / cm 3 Carbon fiber preform;

[0050] (5) First, the carbon fiber preform is subjected to pyrolytic carbon densification treatment using a chemical vapor infiltration process and the density is increased to 1.0 g / cm 3 Then, the carbon fiber preform is subjected to resin carbon densification treatment by resin impregnation carbonization process and the density is increased to 1.50g / cm 3 , then a carbon / carbon composite material crucible body 1 is obtained;

[0051] The parameters of the chemical vapor infiltration process are as follows: propylene is used as the carbon source gas, the flow rate of the carbon source gas is 10 L / min, the deposition temperature is 900°C, and the total deposition time is 80 h;

[0052] The parameters of the resin impregnation carbonization process are as follows: furfural resin is used as the impregnating agent, impregnated at an impregnation pressure of 1.0 MPa for 0.5 h, then cured at a curing temperature of 100 °C for 1 h, and then carbonized at a carbonization temperature of 900 °C for 2 h, and the heating rate of the curing and carbonization process is 10 °C / h;

[0053] (6) The carbon / carbon composite crucible body 1 is first immersed in furfural resin, immersed for 0.5 h at an immersion pressure of 1.0 MPa, then heated to 100°C at a heating rate of 1°C / h and cured at 100°C for 3 h, and then heated to 900°C at a heating rate of 1°C / h and carbonized at 900°C for 5 h, thereby forming a glassy carbon coating 2 with a thickness of 50 μm on the inner surface of the carbon / carbon composite crucible body 1;

[0054] (7) A yttrium oxide coating 3 with a thickness of 500 μm is prepared on the glassy carbon coating 2 by a plasma spraying process, and the preparation of the crucible is completed accordingly, such as Figure 1 As shown;

[0055] The process parameters of plasma spraying include: the particle size of yttrium oxide powder is 100 μm, the pressure of carrier gas (such as nitrogen) is 3.0 MPa, the pressure of auxiliary gas (such as hydrogen) is 2.0 MPa, the current is 900 A, the voltage is 120 V, and the spraying distance is 30 mm.

[0056] The crucible prepared in this embodiment is used to pull silicon rods in a single crystal furnace, and the crucible coating is kept stable for 170 hours (when the crystal is pulled continuously in the crucible, when the liquid level is stable and no bubbles overflow, it indicates that the coating is stable; when bubbles escape, it indicates that the coating is invalid). Within the crucible coating stability time range, the carbon content and oxygen content of the silicon wafer after cutting are tested to verify the carbon barrier performance and purity performance of the crucible. According to the test results, the carbon content is 13.70×10 16 atoms / cm 3 , oxygen content is 1.67×10 17 atoms / cm 3 .

[0057] Example 2

[0058] The integrated carbon / carbon composite material crucible containing the yttria coating 3 specifically comprises the following preparation steps:

[0059] (1) A carbon fiber mesh is needle-punched and laid on a wooden core mold to form a mesh layer;

[0060] Among them, the carbon fiber mesh tire is made of short-cut carbon fiber with a surface density of 300g / m 2 The felt has a needle density of 30 needles / cm 2 , the needling depth is 8 mm; the wooden core mold is made based on the inner surface structure and size of the integrated crucible;

[0061] (2) Spray a layer of furfural resin on the surface of the web layer at a spray volume of 1.0 L / cm 2 , forming a resin layer; at this time, the web layer after spraying the furfural resin is a ply unit (comprising the web layer in step (1) and the resin layer in step (2)), and the thickness of the ply unit is 8 mm;

[0062] (3) Repeating steps (1) to (2) multiple times, forming an alternating stacking structure of a web layer followed by a resin layer on the surface of the resin layer in step (2) (i.e., stacking multiple layer units on the layer unit formed in step (2)), until the desired thickness of the preform is reached after the last spraying of the resin, thereby obtaining a preform precursor;

[0063] According to the structure of the integrated crucible, the crucible is divided into a straight section, a R-angle transition section, and a bottom surface of the crucible in sequence from the upper part to the lower part along its depth direction. Different numbers of layering units are used to make the thickness of the straight section, the thickness of the R-angle transition section, and the thickness of the bottom surface of the crucible 350 mm, 500 mm, and 600 mm, respectively.

[0064] (4) The wooden core mold in the preform precursor obtained in step (3) was replaced with a graphite core mold, and then placed under a pressure of 2.0 MPa and a temperature of 180° C. for curing for 4 h to obtain a density of 0.40 g / cm 3 Carbon fiber preform;

[0065] (5) First, the carbon fiber preform is subjected to pyrolytic carbon densification treatment using a chemical vapor infiltration process and the density is increased to 1.10 g / cm 3 Then, the carbon fiber preform is subjected to resin carbon densification treatment by resin impregnation carbonization process and the density is increased to 1.60g / cm 3 , then a carbon / carbon composite material crucible body 1 is obtained;

[0066] The parameters of the chemical vapor infiltration process are as follows: natural gas is used as the carbon source gas, the flow rate of the carbon source gas is 30 L / min, the deposition temperature is 1000 °C, and the total deposition time is 100 h;

[0067] The parameters of the resin impregnation carbonization process are as follows: phenolic resin is used as the impregnating agent, impregnated for 3 h at an impregnation pressure of 2.0 MPa, then cured at a curing temperature of 200 °C for 6 h, and then carbonized at a carbonization temperature of 950 °C for 4 h. The heating rate of the curing and carbonization process is 15 °C / h;

[0068] (6) The carbon / carbon composite crucible body 1 is first immersed in phenolic resin at an immersion pressure of 2.0 MPa for 1.5 h, then heated to 200° C. at a heating rate of 2° C. / h and cured at 200° C. for 4 h, then heated to 1000° C. at a heating rate of 3° C. / h and carbonized at 1000° C. for 7 h, thereby forming a glassy carbon coating 2 with a thickness of 180 μm on the inner surface of the carbon / carbon composite crucible body 1;

[0069] (7) preparing a yttrium oxide coating 3 with a thickness of 300 μm on the glassy carbon coating 2 by a plasma spraying process, and completing the preparation of the crucible accordingly;

[0070] Among them, the process parameters of plasma spraying include: the particle size of yttrium oxide powder is 55μm, the carrier gas (such as nitrogen) pressure is 1.8MPa, the auxiliary gas (such as hydrogen) pressure is 1.0MPa, the current is 600A, the voltage is 80V, and the spraying distance is 100mm.

[0071] The crucible prepared in this embodiment is used to pull silicon rods in a single crystal furnace, and the crucible coating is kept stable for 140 hours (when the crystal is pulled continuously in the crucible, when the liquid level is stable and no bubbles overflow, it indicates that the coating is stable; when bubbles escape, it indicates that the coating is invalid). Within the crucible coating stability time range, the carbon content and oxygen content of the silicon wafer after cutting are tested to verify the carbon barrier performance and purity performance of the crucible. According to the test results, the carbon content is 22.40×10 16 atoms / cm 3 , oxygen content is 2.16×10 17 atoms / cm 3 .

[0072] Example 3

[0073] The integrated carbon / carbon composite material crucible containing the yttria coating 3 specifically comprises the following preparation steps:

[0074] (1) A carbon fiber mesh is needle-punched and laid on a wooden core mold to form a mesh layer;

[0075] Among them, the carbon fiber mesh tire is made of short-cut carbon fiber with a surface density of 500g / m 2 The felt has a needle density of 50 needles / cm 2 , the needle puncture depth is 10mm; the wooden core mold is made based on the inner surface structure and size of the integrated crucible;

[0076] (2) Spray a layer of phenolic resin on the surface of the mesh layer at a spray volume of 1.5L / cm 2 , forming a resin layer; at this time, the web layer after spraying the phenolic resin is a ply unit (including the web layer in step (1) and the resin layer in step (2)), and the thickness of the ply unit is 10 mm;

[0077] (3) Repeating steps (1) to (2) multiple times, forming an alternating stacking structure of a web layer followed by a resin layer on the surface of the resin layer in step (2) (i.e., stacking multiple layer units on the layer unit formed in step (2)), until the desired thickness of the preform is reached after the last spraying of the resin, thereby obtaining a preform precursor;

[0078] According to the structure of the integrated crucible, the crucible is divided into a straight section, a R-angle transition section, and a bottom surface of the crucible in sequence from the upper part to the lower part along its depth direction. Different numbers of layering units are used to make the thickness of the straight section, the thickness of the R-angle transition section, and the thickness of the bottom surface of the crucible 500 mm, 600 mm, and 800 mm, respectively.

[0079] (4) The wooden core mold in the preform precursor obtained in step (3) was replaced with a graphite core mold, and then placed under a pressure of 3.0 MPa and a temperature of 100° C. for curing for 5 h to obtain a density of 0.50 g / cm 3 Carbon fiber preform;

[0080] (5) First, the carbon fiber preform is subjected to pyrolytic carbon densification treatment using a chemical vapor infiltration process and the density is increased to 1.20 g / cm 3 Then, the carbon fiber preform is subjected to resin carbon densification treatment by resin impregnation carbonization process and the density is increased to 1.70g / cm 3 , then a carbon / carbon composite material crucible body 1 is obtained;

[0081] The parameters of the chemical vapor infiltration process are as follows: natural gas is used as the carbon source gas, the flow rate of the carbon source gas is 50 L / min, the deposition temperature is 1100°C, and the total deposition time is 120 h;

[0082] The parameters of the resin impregnation carbonization process are as follows: furfural resin is used as the impregnating agent, impregnated at an impregnation pressure of 3.0 MPa for 5 h, then cured at a curing temperature of 300 °C for 10 h, and then carbonized at a carbonization temperature of 1000 °C for 6 h. The heating rate of the curing and carbonization process is 20 °C / h;

[0083] (6) The carbon / carbon composite crucible body 1 is first immersed in phenolic resin at an immersion pressure of 3.0 MPa for 2 h, then heated to 300° C. at a heating rate of 3° C. / h and cured at 300° C. for 5 h, then heated to 1100° C. at a heating rate of 5° C. / h and carbonized at 1100° C. for 10 h, thereby forming a glassy carbon coating 2 with a thickness of 300 μm on the inner surface of the carbon / carbon composite crucible body 1;

[0084] (7) preparing a yttrium oxide coating 3 with a thickness of 100 μm on the glassy carbon coating 2 by a plasma spraying process, and completing the preparation of the crucible accordingly;

[0085] Among them, the process parameters of plasma spraying include: the particle size of yttrium oxide powder is 10μm, the carrier gas (such as nitrogen) pressure is 0.2MPa, the auxiliary gas (such as hydrogen) pressure is 0.1MPa, the current is 300A, the voltage is 40V, and the spraying distance is 180mm.

[0086] The crucible prepared in this embodiment is used to pull silicon rods in a single crystal furnace, and the crucible coating is kept stable for 110 hours (crystal pulling is continued in the crucible. When the liquid level is stable and no bubbles overflow, it indicates that the coating is stable; when bubbles escape, it indicates that the coating is invalid). Within the crucible coating stability time range, the carbon content and oxygen content of the silicon wafer after cutting are tested to verify the carbon barrier performance and purity performance of the crucible. According to the test results, the carbon content is 31.26×10 16 atoms / cm 3 , oxygen content is 3.47×10 17 atoms / cm 3 .

[0087] Comparative Example 1

[0088] Based on Example 1, the density obtained in step (5) of Example 1 is 1.50 g / cm 3 The carbon / carbon composite crucible body 1 is placed in a chemical vapor deposition furnace, trichloromethylsilane is used as a silicon source gas, the flow rate of the silicon source gas is 10 L / min, the deposition temperature is 1100° C., and the deposition time is 100 h, and a silicon carbide coating with a thickness of 50 μm is formed on the surface of the carbon / carbon composite crucible body 1; and then a plasma spraying process is used to prepare an aluminum oxide coating with a thickness of 500 μm on the silicon carbide coating, and accordingly an integrated carbon / carbon composite crucible containing a functional coating is obtained;

[0089] The process parameters of plasma spraying include: the particle size of aluminum oxide powder is 100 μm, the pressure of carrier gas (such as nitrogen) is 2.0 MPa, the pressure of auxiliary gas (such as hydrogen) is 1.0 MPa, the current is 800 A, the voltage is 100 V, and the spraying distance is 50 mm.

[0090] Compared with Example 1, the functional coating on the carbon / carbon composite crucible body 1 is a composite of silicon carbide coating and aluminum oxide coating. The crucible prepared in Comparative Example 1 is used to pull silicon rods in a single crystal furnace, and the crucible coating is kept stable for 80 hours (crystal pulling is continued in the crucible. When the liquid level is stable and no bubbles overflow, it indicates that the coating is stable; when bubbles are found to escape, it indicates that the coating has failed). Within the crucible coating stability time range, the carbon content and oxygen content of the silicon wafer after cutting are tested to verify the carbon barrier performance and purity performance of the crucible. According to the test results, the carbon content is 50.32×10 16 atoms / cm 3 , oxygen content is 5.25×10 17 atoms / cm 3 .

[0091] Comparative Example 2

[0092] On the basis of Example 2, except that the steps (1) to (4) of preparing the carbon fiber preform are different, the subsequent steps of densifying the carbon fiber preform and preparing the coating are the same as steps (5) to (7) in Example 2, and an integrated carbon / carbon composite material crucible containing a functional coating is obtained accordingly;

[0093] The specific steps for preparing the carbon fiber preform in this comparative example are as follows:

[0094] (1) First, use a sheet with a thickness of 5 mm and a surface density of 200 g / m 2 The whole carbon cloth is laid on the mesh tire needle-punched layer. After laying a whole carbon cloth, the carbon cloth layer of the straight section of the crucible is formed, and the crucible R angle transition section needs to be superimposed with a layer of small carbon cloth with a thickness of 5mm on the basis of the whole carbon cloth layer to thicken the area to form the carbon cloth layer of the crucible R angle transition section, and the bottom of the crucible also needs to be superimposed with two layers of small carbon cloth with a thickness of 5mm on the basis of the whole carbon cloth layer to thicken the area to form the carbon cloth layer of the bottom of the crucible; then A carbon fiber mesh is laid on the carbon cloth layer in three different areas of the ferry section and the bottom of the crucible to form a carbon fiber mesh layer with a thickness of 4 mm, and then needle-punched and sewn, so that carbon cloth / mesh laminated needle-punched layers with thicknesses of 9 mm, 14 mm, and 19 mm are formed in the three different areas respectively; finally, carbon fiber filaments are continuously wound on the carbon cloth / mesh laminated needle-punched layers in the three different areas along a direction of ±45° with the axial direction of the preform to form a carbon fiber winding layer, and the thickness of the carbon fiber winding layer is 1 mm;

[0095] Among them, according to the structure of the integrated crucible, from the upper part to the lower part of the crucible along its depth direction, it is divided into a crucible straight section, a crucible R angle transition section, and a crucible bottom surface; the carbon cloth / net tire laminated needle-punched layer and the carbon fiber winding layer form a layer unit, and the thickness of the layer unit of the crucible straight section, the thickness of the layer unit of the crucible R angle transition section, and the thickness of the layer unit of the crucible bottom surface are 10mm, 15mm, and 20mm respectively; the needle density of the carbon cloth / net tire laminated needle-punched layer is 10 needles / cm 2 , the acupuncture depth is 5 mm;

[0096] (2) Repeating the operation of step (1) multiple times, forming an alternating stacking structure of carbon cloth / web laminated needle-punched layers followed by carbon fiber winding layers on the surface of the carbon fiber winding layer in step (1) (i.e., stacking multiple layer units on the layer unit formed in step (1)), until the desired thickness of the preform is reached after the last winding of the carbon fiber filaments, thereby obtaining a preform precursor;

[0097] Among them, the thicknesses of the straight section of the crucible, the R-angle transition section of the crucible, and the bottom surface of the crucible in the preform precursor are 150 mm, 225 mm, and 300 mm respectively;

[0098] (3) The preform precursor obtained in step (2) is placed at 80°C for 10 hours to achieve a hardening effect, and a density of 0.40 g / cm 3 Carbon fiber preform.

[0099] The crucible prepared in Comparative Example 2 was used to pull silicon rods in a single crystal furnace, and the crucible coating was kept stable for 50 hours (crystal pulling was continued in the crucible. When the liquid level was stable and no bubbles overflowed, it indicated that the coating was stable; when bubbles escaped, it indicated that the coating failed). Within the crucible coating stability time range, the carbon content and oxygen content of the silicon wafer after cutting were tested to verify the carbon barrier performance and purity performance of the crucible. According to the test results, the carbon content was 21.58×10 16 atoms / cm 3 , oxygen content is 2.14×10 17 atoms / cm 3 .

[0100] Comparative Example 3

[0101] Based on Example 3, the density obtained by directly using the plasma spraying process in step (5) of Example 3 is 1.70 g / cm 3 A yttrium oxide coating 3 with a thickness of 100 μm is prepared on a carbon / carbon composite crucible body 1, and accordingly an integrated carbon / carbon composite crucible containing a functional coating is obtained;

[0102] Among them, the process parameters of plasma spraying include: the particle size of yttrium oxide powder is 10μm, the carrier gas (such as nitrogen) pressure is 0.2MPa, the auxiliary gas (such as hydrogen) pressure is 0.1MPa, the current is 300A, the voltage is 40V, and the spraying distance is 180mm.

[0103] Comparative Example 3 is different from Example 3, except that the glassy carbon coating 2 is omitted. Instead, the yttrium oxide coating 3 is directly prepared on the carbon / carbon composite crucible body 1. The crucible prepared in Comparative Example 3 is used to pull silicon rods in a single crystal furnace, and the crucible coating is kept stable for 40 hours (crystal pulling is continued in the crucible. When the liquid level is stable and no bubbles overflow, it indicates that the coating is stable; when bubbles are found to escape, it indicates that the coating is invalid). Within the crucible coating stability time range, the carbon content and oxygen content of the silicon wafer after cutting are tested to verify the carbon barrier performance and purity performance of the crucible. According to the test results, the carbon content is 122.30×10 16 atoms / cm 3 , oxygen content is 10.38×10 17 atoms / cm 3 .

[0104] In summary, the above are only preferred embodiments of the present invention and are not intended to limit the protection scope of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An integrated carbon / carbon composite crucible with an yttria coating, characterized in that: The crucible comprises a carbon / carbon composite material crucible body, a glassy carbon coating and an yttrium oxide coating, wherein the glassy carbon coating is located between the carbon / carbon composite material crucible body and the yttrium oxide coating; The carbon / carbon composite crucible body is prepared by carbon densification of a carbon fiber preform; the carbon fiber preform is a structure composed of alternately stacked carbon fiber mesh needle-punched layers and resin layers sprayed on the outer surface of the carbon fiber mesh needle-punched layers.

2. The integrated carbon / carbon composite material crucible containing yttria coating according to claim 1, characterized in that: The thickness of the glassy carbon coating is 50 to 300 μm; Or / and, the thickness of the yttrium oxide coating is 100-500 μm.

3. The integrated carbon / carbon composite material crucible containing yttria coating according to claim 1 or 2, characterized in that: The density of the carbon fiber preform is 0.30-0.50 g / cm 3 The density of the carbon / carbon composite crucible body is 1.50-1.70 g / cm 3 .

4. The integrated carbon / carbon composite material crucible containing yttria coating according to claim 1 or 2, characterized in that: The glassy carbon coating is prepared by a resin impregnation carbonization process, which specifically includes the following preparation steps: firstly immersing a carbon / carbon composite material crucible body in a resin, immersing for 0.5 to 5 hours at an impregnation pressure of 1 to 3 MPa, then heating to 100 to 300° C. at a heating rate of 1 to 3° C. / h and curing at 100 to 300° C. for 3 to 5 hours, then heating to 900 to 1100° C. at a heating rate of 1 to 5° C. / h and carbonizing at 900 to 1100° C. for 5 to 10 hours, thereby forming the glassy carbon coating on the inner surface of the carbon / carbon composite material crucible body; Or / and, the yttrium oxide coating is prepared by a plasma spraying process, the process parameters of the plasma spraying include: the particle size of the yttrium oxide powder is 10 to 100 μm, the carrier gas pressure is 0.2 to 3 MPa, the auxiliary gas pressure is 0.1 to 2 MPa, the current is 300 to 900 A, the voltage is 40 to 120 V, and the spraying distance is 30 to 180 mm.

5. The integrated carbon / carbon composite material crucible containing yttria coating according to claim 3, characterized in that: First, the carbon fiber preform is subjected to pyrolytic carbon densification treatment by chemical vapor infiltration process and the density is increased to 1.0-1.20 g / cm 3 Then, the carbon fiber preform is subjected to resin carbon densification treatment by resin impregnation carbonization process and the density is increased to 1.50-1.70 g / cm 3 , then a carbon / carbon composite material crucible body is obtained.

6. The integrated carbon / carbon composite material crucible containing yttria coating according to claim 1, characterized in that: The carbon fiber preform comprises the following specific preparation steps: (1) A carbon fiber web is needle-punched and laid on a core mold to form a web layer; (2) spraying a layer of resin on the surface of the web layer to form a resin layer; (3) Repeating the operations of steps (1) to (2) multiple times, forming an alternating stacking structure of a web layer and a resin layer on the surface of the resin layer in step (2), until the desired thickness of the preform is reached after the last spraying of the resin, thereby obtaining a preform precursor; (4) Curing the preform precursor obtained in step (3) to obtain the carbon fiber preform.

7. The integrated carbon / carbon composite material crucible containing yttria coating according to claim 6, characterized in that: The carbon fiber mat is a thin felt made of chopped carbon fiber with a surface density of 50 to 500 g / m 2 ; Or / and, the needle punching density of the web layer is 10 to 50 needles / cm 2 , acupuncture depth 5 to 10 mm; Or / and, the resin used for spraying the resin layer is furfural resin or phenolic resin; Or / and, the resin spraying amount of the resin layer is 0.5-1.5L / cm 2 .

8. The integrated carbon / carbon composite material crucible containing yttria coating according to claim 6 or 7, characterized in that: The curing conditions are as follows: curing pressure is 1.0-3.0 MPa, curing temperature is 100-250° C., and curing time is 3-5 h.

9. The integrated carbon / carbon composite material crucible containing yttria coating according to claim 6 or 7, characterized in that: According to the structure of the integrated crucible, the crucible is divided into a straight section of the crucible, a R-angle transition section of the crucible, and a bottom surface of the crucible in sequence from the upper part to the lower part along its depth direction. The thickness of the straight section of the crucible in the carbon fiber preform is less than the thickness of the R-angle transition section of the crucible, the thickness of the R-angle transition section of the crucible is less than or equal to the thickness of the bottom surface of the crucible, and the thicknesses of the straight section of the crucible, the R-angle transition section of the crucible, and the bottom surface of the crucible are 200-500 mm, 300-600 mm, and 400-800 mm, respectively.

10. The integrated carbon / carbon composite material crucible containing yttria coating according to claim 9, characterized in that: A layer of web layer and a layer of resin layer constitute a ply unit, and the thickness of a ply unit is 5 to 10 mm; The difference in thickness between the straight section of the crucible, the R-angle transition section of the crucible and the bottom surface of the crucible lies in the different numbers of the layering units.

Citation Information

Patent Citations

  • Crucible and preparation method thereof

    CN103102170A

Cited By

  • Boron nitride-yttrium oxide gradient composite coating for crucible, preparation method and crucible

    CN121272412A

  • Boron nitride crucible and impurity release real-time monitoring method

    CN121428652A